2008
DOI: 10.1346/ccmn.2008.0560511
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Genesis of Smectites in an Alkaline-Saline Environment of Pantanal Wetland, Brazil

Abstract: Smectite formation in alkaline-saline environments has been attributed to direct precipitation from solution and/or transformation from precursor minerals, but these mechanisms are not universally agreed upon in the literature. The objective of this work was to investigate the mineralogy of smectites in the soils surrounding a representative alkaline-saline lake of Nhecolândia, a sub-region of the Pantanal wetland, and then to identify the mechanisms of their formation. Soils were sampled along a toposequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 44 publications
5
65
1
16
Order By: Relevance
“…In this context, the Fe-mica (Furquim et al, 2010a;Barbiero et al, 2016), whereas alkalinity is involved in the formation of other clay minerals and calcite. The cations Ca 2+ and Mg 2+ are controlled by the formation of Mg-calcite with about 5 % Mg (Barbiero et al, 2008) and Mg-smectites of stevensite and saponite types (Furquim et al, 2008;2010b). Since the waters evolve in a sodicalkaline pathway, the salinity range is associated with a wide range in pH values, which affects both surface water (5.5 < pH 5 < 10.5) and lake sediments (5.7 < pH < 9.9).…”
Section: Diversity Of Surface Watermentioning
confidence: 99%
“…In this context, the Fe-mica (Furquim et al, 2010a;Barbiero et al, 2016), whereas alkalinity is involved in the formation of other clay minerals and calcite. The cations Ca 2+ and Mg 2+ are controlled by the formation of Mg-calcite with about 5 % Mg (Barbiero et al, 2008) and Mg-smectites of stevensite and saponite types (Furquim et al, 2008;2010b). Since the waters evolve in a sodicalkaline pathway, the salinity range is associated with a wide range in pH values, which affects both surface water (5.5 < pH 5 < 10.5) and lake sediments (5.7 < pH < 9.9).…”
Section: Diversity Of Surface Watermentioning
confidence: 99%
“…2B) are summarized below and more fully discussed by Furquim et al (2008). The soil consists of a pale brown (10YR 6/3), single grain, sand surface material (horizon 1), which is laterally replaced toward the lake by a dark gray (10YR 4/1), mostly prismatic, loamy sand, surface material, rich in decomposed algae (horizon 2).…”
Section: Study Areamentioning
confidence: 99%
“…1B) was carried out by our research team, the results of which are beginning to be disseminated (e.g. Furquim et al, 2008). In spite of the extensive number of saline lakes in the Nhecolândia, our studies represent a pioneering effort in understanding the silt and clay mineralogy in these landscapes.…”
Section: Introductionmentioning
confidence: 98%
“…Less commonly considered are solutes such as Si, Ca and Mg which have the potential to accumulate in mineral forms. Research conducted in the Okavango Delta, Botswana (McCarthy and Metcalfe, 1990;McCarthy et al, 1993), and the Pantanal, Brazil (Barbiero et al, 2002;Furquim et al, 2008), has shown that large wetland systems can accumulate significant quantities of solutes. Mass balance calculations indicate that chemical accumulation is the dominant aggradational process occurring in the Okavango basin, where it is responsible for shaping the structure and function of this ecosystem (McCarthy and Metcalfe, 1990).…”
Section: Introductionmentioning
confidence: 99%